Systematic review with meta‐analysis: association between Helicobacter pylori CagA seropositivity and odds of inflammatory bowel disease. Issue 2 (5th June 2019) - Tepler, Adam; Narula, Neeraj; Peek, Richard M.; Patel, Anish; Edelson, Cyrus; Colombel, Jean‐Frederic; Shah, Shailja C.
Summary: Background: Accumulating data support a protective role of Helicobacter pylori against inflammatory bowel diseases (IBD), which might be mediated by strain‐specific constituents, specifically cagA expression. Aim: To perform a systematic review and meta‐analysis to more clearly define the association between CagA seropositivity and IBD. Methods: We identified comparative studies that included sufficient detail to determine the odds or risk of IBD, Crohn's disease (CD) or ulcerative colitis (UC) amongst individuals with vs without evidence of cagA expression (eg CagA seropositivity). Estimates were pooled using a random effects model. Results: Three clinical studies met inclusion criteria. cagA expression was represented by CagA seropositivity in all studies. Compared to CagA seronegativity overall, CagA seropositivity was associated with lower odds of IBD (OR 0.31, 95% CI 0.21‐0.44) and CD (OR 0.25, 95% CI 0.17‐0.38), and statistically nonsignificant lower odds for UC (OR 0.68, 95% CI 0.35‐1.32). Similarly, compared to H pylori non‐exposed individuals, H pylori exposed, CagA seropositive individuals had lower odds of IBD (OR 0.26, 95% CI 0.16‐0.41) and CD (OR 0.23, 95% CI 0.15‐0.35), but not UC (OR 0.66, 0.34‐1.27). However, there was no significant difference in the odds of IBD, CD or UC between H pylori exposed, CagA seronegative and H pylori non‐exposed individuals. Conclusion: We found evidence for a significant association between CagA seropositive H pylori exposure and reduced odds of IBD, particularly CD, but not for CagA seronegative H pylori exposure. Additional studies are needed to confirm these findings and define underlying mechanisms.